Stakeholder Mapping in the Management in Lingga Isaq Hunting Park Protected Area, Aceh Tengah - Cut Maila Hanum (STMIK Indonesia Banda Aceh, 2024)
Stakeholder mapping is an important step in managing conservation areas to understand and involve interested parties in decision making. Bur Lingga Isaq Park in Central Aceh is a conservation area that has high biodiversity and is important to preserve. This research aims to carry out stakeholder mapping in the management of Bur Lingga Isaq Park, identify the interests and roles of each stakeholder, and evaluate their level of involvement in decision making regarding conservation areas. The research methods used include document analysis, interviews, and participant observation. The collected data was analyzed descriptively and using stakeholder analysis tools such as interest and power matrices. The research results show that there are several stakeholders involved in the management of Bur Lingga Isaq Park, including local government, local communities, non-government organizations, and educational institutions. Their interests include economic, social, cultural and conservation aspects. The level of stakeholder involvement varies, with some stakeholders having a more dominant role in decision making. These findings provide valuable insights for conservation area managers in strengthening collaboration with stakeholders and ensuring continued participation in decision making. In the context of Bur Lingga Isaq Park, an inclusive and sustainable framework is needed to ensure successful management of conservation areas. This research also provides a basis for further studies in identifying more effective and sustainable management strategies by involving diverse stakeholders and interests in the management of conservation areas.